Antimicrobial Resistance In Poultry Bacterial Flora: A Comparative Analysis Of Two Farms In Thiruvananthapuram District (The Review of Diabetic Studies, 2025)
The increasing demand for poultry products has led to the excessive use of antibiotics in the poultry industry, both as growth promoters and as disease preventives. The practice significantly contributed to the transformation of poultry farms as reservoirs of antimicrobial-resistant (AMR) bacteria and resistance genes that can jeopardize the global healthcare industry. In this study, poultry litter samples were collected from two farms located at distinct zones of Thiruvananthapuram district, Kerala, India. A total of 28 AMR bacterial strains were isolated, with selected potent strains further characterized by 16S rRNA sequencing. The draft assemblies were deposited in GenBank. Comparative evaluation of antimicrobial resistance patterns between the poultry farms located at Ayiroor and Vizhinjam revealed both similarities and site-specific differences, likely influenced by variations in management practices, antibiotic usage, environmental conditions, and biosecurity measures. Resistance to penicillin and ampicillin was consistently observed across both sites, underscoring the reduced efficacy of β-lactam antibiotics in poultry-associated isolates.These findings highlight the urgent need for surveillance and detailed molecular characterization of resistant strains to mitigate the growing public health burden of antimicrobial resistance.